(untitled) (Bangladesh Journal of Pharmacology, 2015)
Ruellia species are traditionally used for the treatment of flu, fever and inflammation. The aim of this study was to evaluate the anticancer activity of Ruellia squarrosa extracts against human prostate cancer (PC3) cell line. Dichloromethane and methanol extracts of aerial and root parts of the plant were made by maceration. Anticancer activity was estimated by MTT assay and percentage inhibition of cells was calculated. Results of MTT showed that 30 mg/ml of dichloromethane extract of root parts of the plant showed moderate anticancer activity (58% inhibition) against PC3 cell line with IC50 15.4 ± 0.3. It was concluded that R. squarrosa (root) possesses anticancer activity against human prostate cancer (PC3) cell line.